Positive Associations between Adipocyte Fatty Acid-Binding Protein Level and Central Arterial Stiffness in Peritoneal Dialysis Patients - Cheng-Hao Sung; Bang-Gee Hsu; Jen-Pi Tasi; Chih-Hsien Wang; Chiu-Huang Kuo (International Journal of Hypertension)
Background. Adipocyte fatty acid-binding protein (A-FABP) plays essential roles in lipolysis, insulin resistance, and atherosclerosis. This study aimed to evaluate the relationship between serum A-FABP levels and carotid-femoral pulse wave velocity (cfPWV) in peritoneal dialysis (PD) patients. Methods. This study obtained fasting blood samples from 76 PD patients. A validated tonometry system was used to measure cfPWV. Patients with cfPWV values >10 m/s were classified into the high arterial stiffness group, whereas patients with values ≤10 m/s were classified into the low arterial stiffness group, according to the ESH-ESC 2013 guidelines. Serum A-FABP levels were measured using a commercial enzyme-linked immunosorbent assay kit. Results. Twenty-five (32.9%) of the 76 PD patients were classified in the high arterial stiffness group. Compared with the patients in the low arterial stiffness group, the high arterial stiffness group was older (P = 0.002) and had a longer PD vintage (P = 0.011), higher diastolic blood pressure (DBP, P = 0.036), higher fasting glucose levels (P = 0.012), higher serum C reactive protein levels (P = 0.001), and higher serum A-FABP levels (P < 0.001). A multivariate logistic regression analysis of the factors significantly associated with central arterial stiffness revealed that A-FABP (odds ratio (OR): 1.165, 95% confidence interval (CI): 1.056–1.284, P = 0.002), age (OR: 1.423, 95% CI: 1.153–1.757, P = 0.001), PD vintage (OR: 1.049, 95% CI: 1.015–1.085, P = 0.005), and DBP (OR: 1.152, 95% CI: 1.033–1.285, P = 0.011) were independent predictors of central arterial stiffness in PD patients. Furthermore, serum A-FABP levels (β = 0.476, adjusted R2 change: 0.197, P < 0.001) were significantly positively correlated with cfPWV according to the multivariable forward stepwise linear regression analysis. Conclusions. A-FABP levels are an independent marker of central arterial stiffness in PD patients.